In the aftermath of the German labor market reforms, is there a qualitative/quantitative trade-off? - Joachim Möller (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2014)
This paper argues that the German labor market reforms implemented in 2003–2005 were successful, according to the main quantitative indicator of labor market conditions. Long-term unemployment decreased substantially in the years after the reform, and the trend of continuously increasing systemic unemployment was reversed. At the same time, the extreme shock to the GDP incurred by the world recession in 2008/2009 left only minor traces in the German labor market. Employment climbed to an all-time high, and several regions, especially Southern Germany, are close to full employment. One should also stress that youth unemployment in the country is among the lowest in Europe. The evidence from several qualitative indicators of labor market conditions, however, is less clear. Since 2005, these different indicators tell both negative and positive stories. On the positive side, the German 'job miracle' could have played a role in this context. Even during the sharpest recession in the post-war period, employment was stable. My interpretation is that this ameliorated the perceived job stability for many workers. On the negative side, the wage growth for many groups of workers is unsatisfactory. Wage inequality has risen substantially. Today, the size of the low-pay sector in Germany is higher than that in almost all other European countries. I argue that the increase in wage dispersion has gone too far. It was not a necessary condition for the improvement of the employment rate but was instead an unintended by-product of the reforms. Therefore, this side effect can be corrected without jeopardizing the indisputable employment rate successes.
Keywords: J10; J28; J31; 330; labor market reforms; unemployment; inequality; quality of jobs